Tingkat Pendidikan dan Prestasi Kerja terhadap Promosi Jabatan pada Badan Keuangan - Pahlan Pahlan (IPM2KPE, 2021)
This study aimed to analyze the influence of high education and job performance on job promotion at the Lahat Regency Regional Financial Board. The sample used was the employees of the Lahat Regency Regional Finance Agency, where the example set in this study was 40 respondents using the random sampling method. The technical analysis used was the F test and the T-test. Based on the statistical test, the level of education variable had a significant effect on job promotion, and the job performance variable has a significant impact on job promotion. Keywords: Job Performance, Job Promotion, Education Level